HOW TO SURVIVE IN THE MIDDLE OF COMPETITIVE MARKET:CASE STUDY OF TERAS BY AKININI - Erick Chandra, Alexander; Shelvi (Jurnal Administrasi Bisnis, 2025)
Bandung is one of the cities in Indonesia with many cafes, and data from Toffin Indonesia (2023) shows that Bandung is the third-largest city in terms of coffee consumers in Indonesia. The Statistical Center of West Java Province (2018) recorded 467 coffee shops or cafes in Bandung in 2018. Intense competition drives companies to design effective and long-term strategies. This research aims to create the most ideal competitive strategy for Téras by Akinini by minimizing weaknesses and maximizing strengths to excel over competitors. The analysis is conducted using a descriptive method with a case study approach, collecting data through interviews and document studies. The "Best Cost Provider" strategy is chosen as the best option, focusing on the company's development in delivering value to customers with broad coverage. It also considers customer expectations regarding quality, cost, environment, and friendlier pricing. Implications of this strategy include improving quality and service to customers, enhancing competitiveness in the market. Additionally, this strategy can increase brand awareness and provide the company with an attractive characteristic to reach a broader market.